037 New insight into dysautonomia in GFAP astrocytopathy. Issue 6 (27th May 2022) - Goh, Yee Yen; Koay, Shiwen; Goodall, Jack; Oommens, Grace; Ingle, Gordon; Parris, Victoria; Iodice, Valeria; Swanton, Josephine; McNamara, Patricia
Abstract : A 17yo Filipino man presented with a rapid onset meningoencephalitic illness, dysautonomia (cardiovas- cular and genitourinary), neuropsychiatric, myoclonus and cerebellar symptoms. Examination revealed lower limb proprioceptive loss and areflexia. CSF showed lymphocytosis, hypoglycorrachia and glial fibrillary acidic protein (GFAP) antibodies. MRI head was normal on D4 and D11, but repeat imaging (D25) showed a reversible splenial T2 hyperintensity, which improved by D40. Neurophysiology showed a sensory neuronopathy. Autonomic function testing confirmed sympathetic cardiovascular failure. Pupillometry showed bilateral Horner's indicating further sympathetic deficit. Dynamic sweat testing showed evidence of post-ganglionic sudomotor dysfunction. He received treatment with IV methylprednisolone followed by a prednisolone taper with good response. GFAP is an intracytoplasmic protein, found in astrocytes, unmyelinated nerve fibres as well as dorsal root ganglia, in keeping with our patient's clinical presentation. However, literature review shows signifi- cant heterogenicity in presentation and pathogenicity of the GFAP antibody is unclear, as it could be a bystander protein. Dysautonomia is reported in 24–57% of GFAP astrocytopathy, but has not been well-characterised. We describe the first in-depth autonomic testing in GFAP astrocytopathy which shows sympathetic cardio- vascular failure and evidence of sudomotor post-ganglionic dysfunction. yeeyen.goh@nhs.net|ABN Bursary